Biofuel development in Malaysia: Challenges and future prospects of palm oil biofuel - Akop, Mohd Zaid; Jikol, Favian; Salim, Mohd Azli; Mohamed Arifin, Yusmady; Herawan, Safarudin Gazali (Universiti Malaysia Perlis, 2022)
Biofuels have received a lot of interest as a result of rising energy demand which caused rapid depletion of fossil fuels and growing worries about greenhouse gas emissions. Biofuels, unlike other renewable energy sources, can supply liquid fuels, which are necessary for transportation. In this review study, the main focus is the scenario of palm oil biofuel development in Malaysia, which involves the future prospect and challenges faced by the country to fully-utilize the potential of palm oil as a renewable energy. Even with the primary driving policy, the National Biofuel Policy 2006, it is found that as of the year 2020, Malaysia is still lacking in pace and technologies in inventing top-notch quality biofuel. Although the number of articles published in the subject of biofuels is increasing, more study is required to explain current technology and its benefits, especially in Malaysia, the world's second-largest producer of oil palm.